2014
DOI: 10.1186/1748-717x-9-147
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of non-small cell lung cancer patients with bone oligometastases treated concurrently with thoracic three-dimensional radiotherapy and chemotherapy

Abstract: BackgroundTo evaluate the efficacy of three-dimensional radiotherapy for non-small cell lung cancer (NSCLC) patients with bone metastases.MethodsClinical data for 95 NSCLC patients with bone metastases were collected and prognostic factors were analyzed. All patients received radiation to their thoracic primary tumor and ≥2 cycles of chemotherapy.ResultsOf these 95 patients, 47 patients had only bone metastases and 48 had both bone metastases and other organ metastases. Univariate analysis showed that factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…There was one large study ( n = 2176), although it was retrospective and a nonconsecutive case series (Level 3iii) [ 76 ]. Of the remaining 17 studies, two were population-based consecutive case series (Level 3i) [ 82 , 83 ], two were non population–based consecutive case series (Level 3ii) [ 84 , 85 ], and twelve were nonconsecutive case series (Level 3iii) [ 76 , 86 97 ], one of which was prospective [ 98 ]. Therapies given varied not only among the studies but within most of them as well, for patients with diversely defined oligometastases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was one large study ( n = 2176), although it was retrospective and a nonconsecutive case series (Level 3iii) [ 76 ]. Of the remaining 17 studies, two were population-based consecutive case series (Level 3i) [ 82 , 83 ], two were non population–based consecutive case series (Level 3ii) [ 84 , 85 ], and twelve were nonconsecutive case series (Level 3iii) [ 76 , 86 97 ], one of which was prospective [ 98 ]. Therapies given varied not only among the studies but within most of them as well, for patients with diversely defined oligometastases.…”
Section: Introductionmentioning
confidence: 99%
“…Overall survival endpoints (level A) were reported in all but one study [ 90 ], however stronger study designs would have shown whether the survival endpoints were significant. OS was reported as MOS (11.7 [ 82 ], 17 [ 94 ], 20 [ 83 ], 26.4 [ 92 ], and 41months [ 91 ] and at four intervals in the remaining studies: 5-year (29.4% [ 84 ], 8.3–86% [ 76 ], 44.7% [ 98 ], 38% [ 96 ], 36% [ 86 ], and 24% [ 87 ]), 3-year (17.5% [ 81 ], 25% [ 85 ], and 15.8% [ 97 ]), 2-year (24% [ 93 ]and 38% [ 89 ]), 18-month (52.9%) [ 88 ] and 1-year (67% [ 80 ]and 75% [ 95 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical incidence for metastatic NSCLC among NSCLC patients is approximately 50%. Metastatic NSCLC is more common in older patients than in younger patients ( 12 ). This is because, in elderly patients, the disease is at a more advanced stage at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer-associated death worldwide ( 1 ), among which non-small cell lung cancer (NSCLC) represents about 85% of all cases ( 2 , 3 ). More than half of the NSCLC patients initially diagnosed with distant metastases ( 4 ). Mehta et al reported that ( 5 , 6 ) patients with metastatic NSCLC could remain relatively stabilization and not be widely disseminated.…”
Section: Introductionmentioning
confidence: 99%